Essential Concepts for the Management of Metastatic Spine Disease: What the Surgeon Should Know and Practice. Issue 1 (May 2019) - Barzilai, Ori; Boriani, Stefano; Fisher, Charles G.; Sahgal, Arjun; Verlaan, Jorrit Jan; Gokaslan, Ziya L.; Lazary, Aron; Bettegowda, Chetan; Rhines, Laurence D.; Laufer, Ilya
Study Design: Literature review. Objective: To provide an overview of the recent advances in spinal oncology, emphasizing the key role of the surgeon in the treatment of patients with spinal metastatic tumors. Methods: Literature review. Results: Therapeutic advances led to longer survival times among cancer patients, placing significant emphasis on durable local control, optimization of quality of life, and daily function for patients with spinal metastatic tumors. Recent integration of modern diagnostic tools, precision oncologic treatment, and widespread use of new technologies has transformed the treatment of spinal metastases. Currently, multidisciplinary spinal oncology teams include spinal surgeons, radiation and medical oncologists, pain and rehabilitation specialists, and interventional radiologists. Consistent use of common language facilitates communication, definition of treatment indications and outcomes, alongside comparative clinical research. The main parameters used to characterize patients with spinal metastases include functional status and health-related quality of life, the spinal instability neoplastic score, the epidural spinal cord compression scale, tumor histology, and genomic profile. Conclusions: Stereotactic body radiotherapy revolutionized spinal oncology through delivery of durable local tumor control regardless of tumor histology. Currently, the major surgical indications include mechanical instability and high-grade spinal cord compression, when applicable, with surgery providing notable improvement in the quality of life and functional status for appropriately selected patients. Surgical trends include less invasive surgery with emphasis on durable local control and spinal stabilization.